International financial integration and U.S. monetary policy : A colloquium sponsored by the Federal Reserve Bank of New York in october 1986 - Pigott, Charles A. (New Yourk Federal Reserve Bank of New York, 1990)
The research is aimed at providing insights to assist monetary authorities and practitioners in adapting their policies to the internationalized financial environment
osc 16/6/17
Loans
Keywords: Financial integration; Monetary policy